1999
DOI: 10.1002/(sici)1521-4087(199904)24:2<99::aid-prep99>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Computer Modeling of Probable Decomposition Reactions: Cyclonitramines

Abstract: SummaryAn approach to computer synthesis and retrosynthesis of organic compounds was formulated, and the CASB (Computer-Assisted Structure Building) software for its computer implementation was created. The approach was evaluated by the example of computer generation of probable routes for reactions of homolytic decomposition. Elementary steps of homolysis reactions were modeled with the use of the``retrosynthetic'' method. Each elementary reaction describes fragments that should be present in the structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…By ab initio and density functional theory (DFT) methods, Habibollahzadeh et al [11] found that a competitive reaction occurred between the symmetrical ring-opening reaction and N-NO 2 bond dissociation, with the formation of three methylene nitramines, which was consistent with the experimental result by Liu et al [3]. Wu et al [12] calculated the bond dissociation energy (BDE) of the N-NO 2 bond and the ring-opening energy of the symmetric ring-breaking by DFT, and concluded that the dissociation pathway of the N-NO 2 bond was the main pathway of the decomposition reaction, which was consistent with the semi-empirical PM3 calculation by Pivina et al [13]. Chakraborty et al [14] studied the N-NO 2 bond dissociation, HONO elimination and symmetrical ring-opening by using the B3LYP/6-31G (d) method, and found that the BDE of the N-NO 2 bond and activation energy of the HONO elimination reaction were 39.0 and 39.2 kcal/mol respectively.…”
Section: Introductionmentioning
confidence: 52%
“…By ab initio and density functional theory (DFT) methods, Habibollahzadeh et al [11] found that a competitive reaction occurred between the symmetrical ring-opening reaction and N-NO 2 bond dissociation, with the formation of three methylene nitramines, which was consistent with the experimental result by Liu et al [3]. Wu et al [12] calculated the bond dissociation energy (BDE) of the N-NO 2 bond and the ring-opening energy of the symmetric ring-breaking by DFT, and concluded that the dissociation pathway of the N-NO 2 bond was the main pathway of the decomposition reaction, which was consistent with the semi-empirical PM3 calculation by Pivina et al [13]. Chakraborty et al [14] studied the N-NO 2 bond dissociation, HONO elimination and symmetrical ring-opening by using the B3LYP/6-31G (d) method, and found that the BDE of the N-NO 2 bond and activation energy of the HONO elimination reaction were 39.0 and 39.2 kcal/mol respectively.…”
Section: Introductionmentioning
confidence: 52%
“…Organic nitrates generate a secondary product (IR absorbance at 1632 cm −1 ) in air that is not produced in a nitrogen atmosphere. The secondary products were identified as α,β-unsaturated carbonyl compounds, which can arise from olefins , or carbonyls , generated in the thermolysis of organic nitrates , (Figure ).…”
Section: Introductionmentioning
confidence: 99%